Aulas de educação física e fatores associados em estudantes do ensino médio : um estudo no contexto sergipano - Santos, Samara Celestino dos (2017)
Objectives: This study aims to analyze high school students participation in physical education (PE) classes and sociodemographic, educational, economics and religious factors association. Methods: This study aims epidemiological and cross-sectional survey data secondary analysis with a sample of 3.992 students (aged 14 to 19) from public high school of Sergipe. It was used a self- administered questionnaire Global Student Health Survey (GSHS). PE classes participation was considered as dependent variable (Participation/Non participation). It was considered independent variables: gender, age bracket, color skin, “who lives with”, grade (high school), study shift, repetition, mother schooling, father schooling, main source of income, Family income, religion and religion practice. To analyze variables association it was used binary logistic regression. Results: Teenagers participation percentual in PE classes was male = 78,2% and female = 71,8%. In the logistic regression, after gender and age bracket adjustsments, it was found association between PE classes participation and “non-white” skin color (OR 1,30; IC95% 1,10–1,54), night study shift (OR 0,62; IC95% 0,54–0,72), “non-catholic” (OR 1,19; IC95% 1,02–1,39), non practicing religion (OR 0,83; IC95% 0,72–0,97). About religion, it was found that there were a reversal between “be catholic or Physical Education classes non participation”. Therefore gender and age variables are, in this study, considered confusion factors to this relation. Conclusion: After adjustments for gender and age bracket variables, it was found an association between PE classes participation and self report color skin “not white”, day shift study, “non-catholic” and practice affiliated religion.